Linguistic Studies on Latin : Selected papers from the 6th International Colloquium on Latin Linguistics (Budapest, 23-27 March 1991). - Herman, József (John Benjamins Pub. Co., 1994)
The volume contains 26 articles (17 in English, 9 in French), selected from the papers presented at the 6th International Colloquim on Latin Linguistics, organized in Budapest. The authors share a common interest in applying to the study of Latin the conceptual framework of contemporary linguistics, mainly, but not exclusively, the theoretical tools of functional grammar and of the newest trends in pragmatics. Most studies envisage Latin in its synchronic functioning, but some papers embrace diachronic processes, from the archaic period to late and even pre-Romance stages. The volume is divided.